Between Danger and Pleasure: Rethinking the Imperilled Filipina Migrant Body in Jose Dalisay’s Soledad’s Sister (KEMANUSIAAN The Asian Journal of Humanities, 2018)
This article explores the complexities and tensions of negotiating female agency and freedom by examining the theme of danger and pleasure through the representation of the Filipina migrant body in Jose Dalisay’s Soledad’s Sister. Of interest here is the Filipina migrant body’s negotiation between the danger posed by the patriarchal systems of the global economy and the pleasure of self- and sexual discovery, for it highlights the empowering possibilities and opportunities that can be found in the very same transnational spaces where dangers also lurk. Subjected to local and global patriarchal discourses – including motherhood and martyrdom – and their prescribed limits, the Filipina migrant body is rendered marginal, displaced and inferior. Despite these limits however, I argue that the migrant body-in-transition should be considered a corporeal “third” space that holds multiple meanings and liminal possibilities that can engender significant changes in identity, voice and agency. Using postcolonial and gender theories, this article problematises the prevailing, authoritative discourses on migrant identity, subjection and subjectivity by showing how the novel undermines essentialist assumptions associated with the stereotyped helper through the exploration of sexual pleasure in the dangerous phallocentric spaces of the global economy.